Effect of maturity in timothy on silage quality and lamb performance - Bernes G.; Hetta M.; Martinsson K. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
This study was conducted to elucidate the effect of harvest time (plant maturity) on forage quality and animal performance in growing lambs. The silage, mostly timothy (Phleum pratense L.) was harvested at three occasions with increasing maturity during summer growth and ensiled in bunker silos. Forage quality was monitored with chemical analysis and with an in vitro gas production (GP) technique, determining the potential degradability of organic matter (OM) and neutral detergent fibre (NDF). There were clear differences between the different cutting times in in vitro degradability of OM and NDF as well as in GP kinetics. The different silages were fed ad libitum to growing lambs. Maturation in timothy had a profound effect on silage intake as well as on live weight gain of the lambs.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)